Nutritional assessment in cirrhotic patients with hepatic encephalopathy - Romeiro, Fernando Gomes [UNESP]; Augusti, Laís [UNESP] (Baishideng Publishing Group, 2015)
Hepatic encephalopathy (HE) is one of the worst complications of liver disease and can be greatly influenced by nutritional status. Ammonia metabolism, inflammation and muscle wasting are relevant processes in HE pathophysiology. Malnutrition worsens the prognosis in HE, requiring early assessment of nutritional status of these patients. Body composition changes induced by liver disease and limitations superimposed by HE hamper the proper accomplishment of exams in this population, but evidence is growing that assessment of muscle mass and muscle function is mandatory due to the role of skeletal muscles in ammonia metabolism. In this review, we present the pathophysiological aspects involved in HE to support further discussion about advantages and drawbacks of some methods for evaluating the nutritional status of cirrhotic patients with HE, focusing on body composition.
Keywords: Anthropometry; Dual-energy X-ray absorptiometry; Electric impedance; Hepatic encephalopathy; Liver cirrhosis; Malnutrition; Muscle strength; Nutrition assessment